Pain tolerance versus competitive success in youth kickboxing - Sobyanin, F. I.; Poidunov, A. A.; Daupaev, M. O.; Malakhov, V. A. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to rate and analyze the pain tolerance versus competitive progress in the youth kickboxing sport.